Optimization of Refining Strategy to Fractionate Various Iraqi Crude Oils into Lighter Fractions - Shakor, Zaidoon M.; Ali, Salah M.; Mohammed, Harith A.; Hassan, Talal F. (Journal of Petroleum Research and Studies, 2018)
The primary objective of this study is to predict optimum refining strategy to fractionate various Iraqi crude oils into lighter fractions depending on market monthly demand along one year. The monthly consumption of gasoline, kerosene and diesel was calculated and genetic algorithm optimization method was used to calculate optimum cut points and blending ratio of three different crude oils (light Basrah, heavy Basrah and Kirkuk). The results prove that manipulation cut points within a year for a blend of three crude oils will decrease 12.8% of distilled crude oil to produce the required amount of light cuts produced by refining single crude oil.